Cost-utility analysis of life-long prophylaxis with recombinant factor VIIIFc vs recombinant factor VIII for the management of severe hemophilia A in Sweden. (3rd April 2018) - Henry, Nathaniel; Jovanović, Jelena; Schlueter, Max; Kritikou, Persefoni; Wilson, Koo; Myrén, Karl-Johan
Abstract: Aims: Prophylaxis with recombinant factor VIII (rFVIII) is the standard of care for severe hemophilia A in Sweden. The need for frequent injections with existing rFVIII products may, however, result in poor adherence to prophylaxis, leading to increased bleeding and long-term joint damage. Recombinant FVIIIFc (rFVIIIFc) is an extended half-life fusion protein which can offer prolonged protection and reduced dosing frequency. The objective of this study was to evaluate the cost-utility of prophylaxis with rFVIIIFc in severe hemophilia A from the perspective of the Swedish health system. Methods: A Markov model was built to estimate lifetime costs and benefits of prophylaxis with rFVIIIFc vs rFVIII products. Clinical outcomes were represented by annualized bleeding rate (ABR) and quality of life via disutility applied to bleeding events and injection frequency. Costs included the cost of FVIII for routine prophylaxis and bleed resolution. The pooled comparator was costed by weighting the cost of individual products by their market share. Results: In the base case, rFVIIIFc was dominant vs the pooled comparator. Savings of SEK 9.0 million per patient resulted from lower factor consumption for prophylaxis and bleed resolution. Fewer bleeds and reduced injection frequency yielded an estimated 0.59 quality-adjusted life years (QALYs). Results were sensitive to drug dosage and robust to variation in other parameters. Probabilistic sensitivity analysis suggested a greater than 85% probability of rFVIIIFc being cost-effective at a willingness-to-pay threshold of 500, 000 SEK/QALY. Limitations: Due to unavailibilty of patient-level data, treatment benefit was based on a non-adjusted indirect comparison. Dosing and treatment outcomes were assumed to persist over the model duration in the absence of long-term outcome data. Conclusion: The results suggest that rFVIIIFc may be a cost-effective option for hemophilia A prophylaxis, generating greater quality of life and reduced costs for the Swedish payer compared to more frequently administered rFVIII alternatives.